Unravelling influential individual level factors during a crowdfunding campaign: insights from the ALS ice bucket challenge - Nisar, Tahir M.; Prabhakar, Guru; Bourlakis, Michael (Elsevier, 2021)
This study aims to identify the factors that drive sharing and donating in a viral crowdfunding campaign. Crowdfunding is a method of raising finance that allows founders of both for-profit and nonprofit social and cultural projects to request funding from multiple people. Using ALS (Amyotrophic Lateral Sclerosis) Ice Bucket Challenge as a case study, we explored the triggering factors for sharing content and donating money that resulted in the campaign’s phenomenal success. The hybridity inherent across crowdfunding models has meant that there are diverse motivations and incentives for people to participate in a crowdfunding campaign. It is therefore important to understand what factors lead social media / online information to reach a wider audience in the shortest possible time. Following a literature review, a theoretical model of motivating factors was developed and tested through an online survey among 469 US participants. The results indicate significant relationships between those who participated / donated and the modeled factors. Personalization and message involvement are the strongest factors for sharing, whereas moral obligation to donate is strongest for donating. By examining the factors that are responsible for sharing and donating simultaneously, we provide a comprehensive assessment of the motivating factors for the campaign’s success.
Keywords: Crowdfunding; Virality; Sharing; Donations; Charity; ALS Ice Bucket Challenge